Primary care requests for anaemia chemistry tests in Spain: potential iron, transferrin and folate over-requesting. Issue 9 (17th February 2017) - Salinas, Maria; López-Garrigós, Maite; Flores, Emilio; Leiva-Salinas, Carlos
Abstract : Aim: To study the regional variability of requests for anaemia chemistry tests in primary care in Spain and the associated economic costs of potential over-requesting. Methods: Requests for anaemia tests were examined in a cross-sectional study. Clinical laboratories from different autonomous communities (AACCs) were invited to report on primary care anaemia chemistry tests requested during 2014. Demand for iron, ferritin, vitamin B12 and folate tests per 1000 inhabitants and the ratios of the folate/vitamin B12 and transferrin/ferritin requests were compared between AACCs. We also calculated reagent costs and the number of iron, transferrin and folate tests and the economic saving if every AACC had obtained the results achieved by the AACC with best practice. Results: 110 laboratories participated (59.8% of the Spanish population). More than 12 million tests were requested, resulting in reagent costs exceeding €16.5 million. The serum iron test was the most often requested, and the ferritin test was the most costly (over €7 million). Close to €4.5 million could potentially have been saved if iron, transferrin and folate had been appropriately requested (€6 million when extrapolated to the whole Spanish population). Conclusions: The demand for and expenditure on anaemia chemistry tests in primary care in Spain is high, with significant regional differences between different AACCs.